The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/02844310500430003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of intralesional injection of triamcinolone acetonide for the treatment of keloid scars in Asian patients

Abstract: We studied the long-term outcome of injection of triamcinolone acetonide into keloid scars in Asian patients. Between 1985 and 2003, we treated 109 keloid scars in 94 patients by injecting 1 to 10?mg of triamcinolone acetonide depending on the size of the lesion at four week intervals. There was little morbidity. Thirty-one patients gave up treatment within 10 injections because of pain and lack of immediate improvement. Improvement in subjective symptoms was seen in 52 of the remaining 63 patients (82%). In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 16 publications
(10 reference statements)
2
65
0
1
Order By: Relevance
“…In our study, the overall remission rate (65%) was somewhat lower than in previous studies. Muneuchi et al also reported less favorable results than the previous studies; there was improvement in subjective symptoms in 82% of patients, but objectively the results were good or better in only 39% of the cases [30].…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations
“…In our study, the overall remission rate (65%) was somewhat lower than in previous studies. Muneuchi et al also reported less favorable results than the previous studies; there was improvement in subjective symptoms in 82% of patients, but objectively the results were good or better in only 39% of the cases [30].…”
Section: Discussionmentioning
confidence: 39%
“…Muneuchi et al used 20-30 injections over 3-5 years, but reported only few local side effects. The concentration of TAC and the injection technique reported in their study did not differ from the technique generally used by professionals treating keloids [30].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…12,13 In the majority of patients, multiple intralesional injections are needed to obtain the desired clinical effect, i.e. flattening of the lesion and cessation of itching.…”
Section: J B Van Rijswijk E a M Mylanusmentioning
confidence: 99%